Legalitas Pakaian Bekas Impor yang Diperjualbelikan Secara Bebas di Indonesia Pasca Berlakunya Undang-Undang Nomor 7 Tahun 2014 Tentang Perdagangan - I Gusti Bagus Suryawan; I Komang Agustina Aditya Putra; Ni Gusti Ketut Sri Astiti (Fakultas Hukum Universitas Warmadewa, 2024)
Illegal importation of used clothing is a common practice in Indonesia. It is not uncommon for used clothing that has been illegally imported to be traded freely. The problems discussed in this study are 1) the legal regulation of imported used clothing according to Law Number 7 of 2014 and 2) the role of the government in overcoming the phenomenon of illegally imported used clothing that is freely traded in Indonesia?. The research method used is normative juridical research method through literature study. The legal materials used are primary legal materials and secondary legal materials. The results of the study stated. Legal arrangements for imported used clothing have been explicitly explained through Article 47 paragraph 1 of Law Number 7 of 2014 concerning trade. The role of the government in overcoming the phenomenon of illegal imports of used clothing that is freely traded in Indonesia is realized through supervisory efforts with the formation of regulations of Law Number 7 of 2014 and enforcement efforts through sanctions against illegal importers and used clothing business actors in Indonesia.